Change in the structure and mechanical properties of Al–Mg–Si alloys caused by the addition of other elements: A comprehensive review - Singh P.; Ramacharyulu D.A.; Kumar N.; Saxena K.K.; Eldin S.M. (My University, 2025)
Understanding 6xxx AA (Al–Mg–Si alloys) relies heavily on structural analysis at the atomic level. Because the nanoscale precipitates that form during artificial ageing essentially strengthen the alloys, it is crucial to lessen the negative effects of Natural Ageing (NA) and enhance the age hardening of Al–Mg–Si alloys. Numerous studies have shown that when different elements are added to 6xxx AA, NA is suppressed. This work includes a thorough and numerical description of the various elements that are added to 6xxx AA. This article gives information on the additional elements Li, Cu, Zn, and Ag that will form new phases and occupy a preferred site in 6xxx AA at different weight percentages. However, between metastable phases, 6xxx AA exhibit different element segregation, which improved the mechanical properties like hardness reported in this review work. Additionally, research on the addition of various other elements, such as Ni, Co, Au, and Cd to 6xxx AA is reported in this review paper to summarise the influence of these elements on the evolution of microstructural features and their correlation with mechanical properties. This area has received very little research and may be used in the future to enhance the mechanical properties of 6xxx AA. By encouraging precipitate nucleation, morphology, and mechanical properties through the addition of foreign elements, the results of this review paper reveal a novel pathway for precipitation hardening. © 2023 The Author(s)